2013
DOI: 10.1002/jbmr.1940
|View full text |Cite
|
Sign up to set email alerts
|

Bone remodeling is regulated by inner ear vestibular signals

Abstract: Bone remodeling allows the conservation of normal bone mass despite constant changes in internal and external environments. The adaptation of the skeleton to these various stimuli leads credence to the notion that bone remodeling is a true homeostatic function, and as such is under the control of specific centers in the central nervous system (CNS). Hypothalamic and brainstem centers, as well as the sympathetic nervous system (SNS), have been identified as regulators of bone remodeling. However, the nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 62 publications
6
33
0
Order By: Relevance
“…Here we confirm that global locomotor activity in the days after transtympanic injection was similar in BVL and SO rats according to one of our recent papers using a similar vestibular lesion model by arsanilate (61). In that previous work we showed that diurnal and nocturnal locomotor activity independently remained at the same level in both groups, whereas rats with BVL suffered from a vestibular syndrome maximal between day 2 and day 7 after lesion compared with unharmed control rats (60).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Here we confirm that global locomotor activity in the days after transtympanic injection was similar in BVL and SO rats according to one of our recent papers using a similar vestibular lesion model by arsanilate (61). In that previous work we showed that diurnal and nocturnal locomotor activity independently remained at the same level in both groups, whereas rats with BVL suffered from a vestibular syndrome maximal between day 2 and day 7 after lesion compared with unharmed control rats (60).…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, if rats with BVL suffer from a vestibular syndrome, their diurnal/nocturnal global locomotor activity remained similar to that of rats in the SO group, but it was more divided within the first days after lesion. This suggests that the sleep/wake state was probably more fragmented; however, the total sleep time might not have changed, and thus would not influence the daily rhythms of Temp and Act (60,61).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observations of group differences in bone volume and density at the distal femur and a reduction of bone formation marker P1NP in animals with stroke–despite similar physical activity patterns between groups—suggest that stroke may suppress bone formation. Based on human stroke studies [10,29], evidence from hind-limb immobilization and unloading in neurologically intact rats [57], and the neural control of bone metabolism [11,12,30], it was hypothesized that MCAo would compromise the microstructure of femurs on the left (paretic) leg. There was no effect of stroke observed on the primary outcome (trabecular bone volume fraction of left femurs), but there were a number of changes in secondary outcomes that may prove to be important findings and should be considered for inclusion in future studies.…”
Section: Discussionmentioning
confidence: 99%